The Little Data Book on External Debt 2012 - World Bank (Washington, DC: World Bank, 2012)
The little data book on external debt, a pocket edition of Global Development Finance 2012: external debt of developing countries contains statistical tables on the external debt of the 129 countries that report public and publicly guaranteed external debt under the debtor reporting system. It also includes tables of selected debt and resource flow statistics for individual reporting countries as well as summary tables for regional and income groups. It is the culmination of a year-long process that requires extensive cooperation from people and organizations around the globe, national central banks, and ministries of finance, major multilateral organizations, and many departments of the World Bank. The little data book on external debt provides a quick reference for users of the Global Development Finance 2012 book, CD-ROM, and online database. The general cutoff date for data is September 2011. The little data book on external debt covers external debt stocks and flows, major economic aggregates, key debt ratios, and the currency composition of long-term external debt for all countries reporting through the debtor reporting system. Terms used in tables are defined in the glossary. The economic aggregates presented in the tables are prepared for the convenience of users. Although debt ratios can provide useful information about developments in debt-servicing capacity, drawing valid conclusions from them requires careful economic evaluation.